Journal for ImmunoTherapy of Cancer - Romero, Pedro
Journal for ImmunoTherapy of Cancer is an open access, peer reviewed journal that encompasses all aspects of tumor immunology and cancer immunotherapy, from basic research through to clinical applications. The journal welcomes submissions in the following sections and other related topics: Basic Tumor Immunology - edited by Cornelis J. Melief Case Reports - edited by Alfred Zippelius Clinical Trials Monitor - edited by Leisha A. Emens Clinical/Translational Cancer Immunotherapy - edited by James L. Gulley Commentary/Editorials - edited by Christian Capitini Guidelines and Consensus Statements – edited by Robert L. Ferris Immunotherapy Biomarkers - edited by Lisa H. Butterfield Reviews - edited by Sandra Demaria and Thomas F. Gajewski.